Conductive material dispersion, and electrode and lithium secondary battery manufactured using same

By using nitrile-based copolymers with oxane, styrene and alkylene unit copolymers in the conductive material dispersion, the problem of increased viscosity of the conductive material dispersion is solved, and the productivity and processability of the electrode are improved.

CN119133451APending Publication Date: 2024-12-13LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411143902.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-05-17
Filing Date
2020-05-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The viscosity of the existing conductive material dispersions increases rapidly when increasing the content of the conductive material, limiting the improvement of conductivity and processability, and low weight average molecular weight dispersants lead to a decrease in storage stability.

Method used

A nitrile-based copolymer is used as the main dispersant, and a copolymer of oxane-based styrene-based units and alkylene-based units is used as the auxiliary dispersant to form a conductive material dispersion, reducing viscosity and increasing solid content.

Benefits of technology

The low viscosity characteristics of the conductive material dispersion are achieved, the productivity, drying efficiency and adhesion of the electrode are improved, and the processability is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005001690350000071
    Figure BDA0005001690350000071
  • Figure BDA0005001690350000072
    Figure BDA0005001690350000072
  • Figure BDA0005001690350000081
    Figure BDA0005001690350000081
Patent Text Reader

Abstract

The present invention relates to a conductive material dispersion, and an electrode and a lithium secondary battery manufactured using the conductive material dispersion, in which the conductive material dispersion comprises a carbon-based conductive material, a main dispersant, an auxiliary dispersant, and a dispersion medium, and the auxiliary dispersant is a copolymer including an oxyalkylene unit and at least one of a styrene unit and an alkylene unit.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of May 12, 2020, application number 202080030812.4, and invention name “Conductive material dispersion, and electrodes and lithium secondary batteries manufactured using the conductive material dispersion” (PCT / KR2020 / 006238, national phase entry date October 22, 2021).

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of Korean Patent Application No. 10-2019-0057722 filed in the Korean Intellectual Property Office on May 17, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to a conductive material dispersion, and an electrode and a lithium secondary battery manufactured using the same. More specifically, the present invention relates to a conductive material dispersion, and an electrode and a lithium secondary battery manufactured using the same, wherein the conductive material dispersion has low viscosity characteristics by using a copolymer including a specific unit as an auxiliary dispersant together with a nitrile-based copolymer as a main dispersant. Background Art

[0005] A secondary battery is a battery that can be used repeatedly through a discharge process that converts chemical energy into electrical energy and a charging process in the opposite direction thereof. A secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator, and generally speaking, the positive electrode and the negative electrode consist of an electrode current collector and an electrode active material layer formed on the electrode current collector. The electrode active material layer is prepared by applying an electrode slurry composition including an electrode active material, a conductive material, a binder, and the like to the electrode current collector, followed by drying, and then rolling.

[0006] The conductive material is used to improve the conductivity of the electrode active material, and fine carbon materials such as carbon black, Ketjen black, fullerene, graphene, carbon nanotube (CNT), and the like are mainly used as the conductive material.

[0007] However, since the conductive material of the carbon material is easily aggregated and unevenly dispersed in the electrode slurry composition, when the electrode is manufactured by using the conductive material of the carbon material, the conductive material cannot be evenly distributed in the electrode active material layer. In order to overcome this limitation, a method has been recently developed in which the conductive material is first mixed with a dispersant such as polyvinyl pyrrolidone (PVP), acrylonitrile-butadiene rubber and the like in a solvent to prepare a conductive material dispersion, and then the conductive material dispersion is applied to the electrode slurry composition.

[0008] However, since the viscosity of the conductive material dispersion using the PVP dispersant rapidly increases when the content of the conductive material increases, there is a limit in increasing the content of the conductive material, and thus, there is a limit in improving conductivity.

[0009] Meanwhile, in order to reduce the viscosity of the conductive material dispersion, it is preferred to use a dispersant having a low weight average molecular weight. However, in the case of an acrylonitrile-butadiene rubber dispersant, there is a problem that when the weight average molecular weight decreases, its storage stability rapidly decreases due to gelation.

[0010] Meanwhile, the solid content of the positive electrode slurry is determined according to the solid content of the conductive material dispersion, and when the solid content of the positive electrode slurry is high, there are effects such as improving productivity, improving electrode drying efficiency and binder migration, improving adhesion, and the like. Therefore, it is preferred to increase the solid content of the conductive material dispersion, but when the solid content increases, the viscosity increases, and therefore, there is a problem in terms of processability.

[0011] Therefore, there is a need to develop a conductive material dispersion having low viscosity characteristics even when the conductive material content is high. Summary of the invention

[0012] Technical issues

[0013] One aspect of the present invention provides a conductive material dispersion having low viscosity characteristics compared with existing conductive dispersions by using a copolymer including specific units as an auxiliary dispersant together with a nitrile-based copolymer dispersant in the conductive material dispersion.

[0014] Another aspect of the present invention provides an electrode and a lithium secondary battery manufactured using the conductive material dispersion.

[0015] Technical Solution

[0016] According to one aspect of the present invention, a conductive material dispersion is provided, which includes a carbon-based conductive material, a dispersant and a dispersion medium, wherein the dispersant includes a main dispersant and an auxiliary dispersant, the main dispersant is a nitrile-based copolymer, and the auxiliary dispersant is a copolymer including an oxyalkylene unit and at least one of a styrene unit and an alkylene unit.

[0017] According to another aspect of the present invention, an electrode is provided, which includes an electrode active material layer formed from an electrode slurry composition, wherein the electrode slurry composition includes an electrode active material, a conductive material dispersion, a binder, and a solvent. In this case, the electrode may be a positive electrode.

[0018] According to another aspect of the present invention, there is provided a lithium secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. In this case, the positive electrode may be the electrode according to the present invention.

[0019] Beneficial Effects

[0020] The conductive material dispersion according to the present invention uses a nitrile-based copolymer together with a copolymer including an oxyalkylene unit and a styrene unit and / or an alkylene unit, and therefore has lower viscosity characteristics than a conductive material dispersion using only a nitrile-based copolymer dispersant. Therefore, the solid content in the conductive material dispersion can be increased compared to the existing conductive dispersion, and as a result, when manufacturing an electrode, there can be effects such as improved productivity, improved electrode drying efficiency and binder migration, improved adhesion, and the like. DETAILED DESCRIPTION

[0021] It will be understood that the terms or words used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in common dictionaries. It will be further understood that, based on the principle that the inventor can appropriately define the meanings of terms or words to best explain the present invention, these terms or words should be interpreted as having a meaning consistent with the meaning in the context of the technical concept of the present invention and the related technology.

[0022] In the present specification, the terms "include", "comprises" or "has" are intended to specify the existence of stated features, quantities, steps, elements, or combinations thereof, but do not exclude the existence or addition of one or more other features, quantities, steps, elements, or combinations thereof.

[0023] In the present specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the adsorption amount of nitrogen gas at liquid nitrogen temperature (77K) using Belsorp-mino II of BEL Japan Co.

[0024] In this specification, "weight average molecular weight (Mw)" refers to a conversion value of standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value converted from a value measured under the following conditions using GPC, and a calibration curve is prepared using standard polystyrene of an Agilent system.

[0025] <Measurement conditions>

[0026] Measuring device: Agilent GPC (Agulent 1200 series, USA)

[0027] Column: Two PL Mixing B connections

[0028] Eluent: Tetrahydrofuran

[0029] Flow rate: 1.0m / min

[0030] Concentration: ~1 mg / mL (100 μL injection)

[0031] Hereinafter, the present invention will be described in more detail.

[0032] Conductive material dispersion

[0033] First, the conductive material dispersion according to the present invention will be described.

[0034] The conductive material dispersion according to the present invention comprises a carbon-based conductive material, a dispersant and a dispersion medium. In this case, the dispersant comprises a primary dispersant and an auxiliary dispersant, the primary dispersant is a nitrile-based copolymer, and the auxiliary dispersant is a copolymer comprising an oxyalkylene unit and at least one of a styrene unit and an aliphatic hydrocarbon unit.

[0035] Hereinafter, each component of the conductive material dispersion according to the present invention will be described in detail.

[0036] (1) Carbon-based conductive materials

[0037] The carbon-based conductive material is used to improve the conductivity of the electrode, and a carbon-based conductive material generally used in the art, for example, carbon nanotube, carbon black, or the like may be used.

[0038] In carbon nanotubes, graphite sheets have a cylindrical shape with a nanometer-scale diameter and have an sp2 bonding structure, and exhibit conductor or semiconductor properties according to the angle and structure at which the graphite surface is rolled. According to the number of bonds forming the wall, carbon nanotubes can be divided into single-walled carbon nanotubes (SWCNT, single-walled carbon nanotube), double-walled carbon nanotubes (DWCNT, double-walled carbon nanotube) and multi-walled carbon nanotubes (MWCNT, multi-walled carbon nanotube). Such carbon nanotubes can be appropriately selected according to the purpose of the dispersion.

[0039] In addition, the carbon nanotube may have a secondary shape in which a plurality of carbon nanotubes are aggregated or arranged. For example, the carbon nanotube may be a bundle-type carbon nanotube in a bundle or rope shape, in which a plurality of carbon nanotubes are arranged or aligned in parallel in a predetermined direction, or may be a spherical or potato-shaped entangled-type carbon nanotube in which entanglement is absent in a specific directionality. In terms of dispersibility, the carbon nanotube is more preferably a bundle-type carbon nanotube.

[0040] Meanwhile, as carbon black, commercially available furnace black, channel black, thermal black, acetylene black, Ketjen black, hollow black or the like may be used. The type of carbon nanotube is not particularly limited.

[0041] The carbon black may be surface treated by methods known in the art as needed. For example, the carbon black may have been surface treated by acetylene gas so as to be free of impurities. In addition, the purity of the carbon black may be 99.5% or higher.

[0042] Meanwhile, the BET specific surface area of ​​the carbon-based conductive material used in the present invention can be 1000 m 2 / g or less, preferably 30-1000m 2 / g. When the BET specific surface area of ​​carbon-based conductive materials is greater than 1000m 2 / g, smooth dispersion may not be achieved.

[0043] Specifically, when the carbon-based conductive material is a carbon nanotube, the BET specific surface area of ​​the carbon nanotube may be 100-1000 m 2 / g, 150-800m 2 / g, 150-500m 2 / g, 150-300m 2 / g, or 150-200m 2 / g.

[0044] When the carbon-based conductive material is carbon black, the BET specific surface area of ​​the carbon black may be 30-1000 m 2 / g, preferably 30-400m 2 / g, more preferably 30-380m 2 / g, even more preferably 30-150m 2 / g.

[0045] At the same time, the content of the carbon-based conductive material in the conductive material dispersion can be 0.1-30% by weight, preferably 1-30% by weight. Specifically, when the carbon-based conductive material is a carbon nanotube, the content of the carbon-based conductive material in the conductive material dispersion can be 0.1-10% by weight, preferably 1-8% by weight, and when the carbon-based conductive material is carbon black, the content of the carbon-based conductive material in the conductive material dispersion can be 1-30% by weight, preferably 1-25% by weight. When the content of the carbon-based conductive material is too low, there may be the following problems: the load is reduced during the manufacture of the electrode, thereby increasing the process cost, and during the manufacture of the electrode, the binder migration occurs, so that the adhesion is reduced. At the same time, when the content of the carbon-based conductive material is too high, there is a problem of increased viscosity of the conductive material dispersion.

[0046] (2) Dispersant

[0047] The conductive material dispersant according to the present invention includes two dispersants. Specifically, the conductive material dispersant according to the present invention includes a nitrile-based copolymer as a main dispersant and a copolymer including an oxyalkylene unit and at least one of a styrene unit and an aliphatic hydrocarbon unit as an auxiliary dispersant.

[0048] 2-1) Main dispersant

[0049] The primary dispersant is to improve the dispersibility of the carbon-based conductive material in the conductive material dispersion, and specifically, may be a copolymer having α,β-unsaturated nitrile-derived units and conjugated diene-derived units. At this time, the conjugated diene-derived units may be partially or completely hydrogenated. The method of hydrogenating the conjugated diene-derived units may be carried out by a hydrogenation method known in the art, for example, by a catalytic hydrogenation reaction using a catalyst system such as Rh, Ru, Pd and IR, and the hydrogenation rate may be adjusted by adjusting the amount of the catalyst, the reaction hydrogen pressure, the reaction time and the like.

[0050] The nitrile-based copolymer can be prepared by copolymerizing an α,β-unsaturated nitrile monomer and a conjugated diene-based monomer and then hydrogenating the C=C double bonds in the copolymer. The polymerization reaction and hydrogenation process of the monomers can be carried out according to typical methods known in the art.

[0051] As the α,β-unsaturated nitrile monomer, for example, acrylonitrile or methacrylonitrile may be used, and any one of them or a mixture of two or more thereof may be used.

[0052] As the conjugated diene-based monomer, for example, a conjugated diene-based monomer having 4 to 6 carbon atoms such as 1,3-butadiene, isoprene, 2,3-methylbutadiene or the like may be used, and any one of them or a mixture of two or more thereof may be used.

[0053] Meanwhile, the weight ratio of the α,β-unsaturated nitrile-derived units: conjugated diene-derived units included in the nitrile-based copolymer may be 10-50:50-90, preferably 20-40:60-80, and more preferably 25-40:60-75. When the content of each unit in the nitrile-based copolymer satisfies the above range, the dispersibility and high temperature performance are excellent. Here, the content of the α,β-unsaturated nitrile-derived units may be the median of the values ​​quantified by measuring the amount of nitrogen generated according to the mill furnace method of JIS K 6364 and calculating its binding amount according to the molecular weight of the α,β-unsaturated nitrile. The content of the conjugated diene-derived units may be the value obtained by subtracting the weight of the α,β-unsaturated nitrile-derived units from the weight of all copolymers.

[0054] Meanwhile, the nitrile-based copolymer of the present invention may have a hydrogenation rate of the conjugated diene-derived units of 80% or more, preferably 90%. This is because, when a dispersant having unhydrogenated conjugated diene units is used, the reactivity with the electrolyte solution may increase due to the double bonds in the conjugated diene, and thus the high temperature performance may deteriorate.

[0055] According to one embodiment, the nitrile-based copolymer may include a repeating unit represented by the following [Formula 1] and a repeating unit represented by the following [Formula 2].

[0056] [Formula 1]

[0057]

[0058] [Formula 2]

[0059]

[0060] At this time, the content of the repeating unit represented by the above [Formula 1] can be 10-50% by weight, preferably 20-40% by weight, and more preferably 25-40% by weight, and the content of the repeating unit represented by the above [Formula 2] can be 50-90% by weight, preferably 60-80% by weight, and more preferably 60-75% by weight.

[0061] Meanwhile, the weight average molecular weight of the primary dispersant may be 10,000-500,000 g / mol, preferably 20,000-400,000 g / mol, more preferably 20,000-300,000 g / mol, and further more preferably 20,000-100,000 g / mol. When the weight average molecular weight of the primary dispersant satisfies the above range, the conductive material can be uniformly dispersed with a small amount of the dispersant, and the solution viscosity can be prevented from excessively increasing when the conductive material is dispersed, which is beneficial to processing.

[0062] 2-2) Auxiliary dispersant

[0063] The auxiliary dispersant is used to improve the dispersibility of the carbon-based conductive material by assisting the primary dispersant, and is a copolymer including an oxyalkylene unit and a styrene unit and / or an alkylene unit.

[0064] The oxyalkylene unit can be represented by Formula 3 below.

[0065] [Formula 3]

[0066]

[0067] In Formula 3 above, R1 is an alkylene group having 1 to 20 carbon atoms, preferably an alkylene group having 2 to 10 carbon atoms, and more preferably an alkylene group having 2 to 5 carbon atoms.

[0068] The oxyalkylene unit may be included in an amount of 5-85 wt%, preferably 9-85 wt%, based on the total weight of the copolymer. When the content of the oxyalkylene unit in the auxiliary dispersant copolymer is greater than 85 wt%, the effect of improving the viscosity of the conductive material dispersion is not significant.

[0069] The styrene unit can be represented by Formula 4 below.

[0070] [Formula 4]

[0071]

[0072] In the above Formula 4, R2 may be hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a combination thereof.

[0073] The content of the styrene unit may be 70 wt% or less, preferably 5-50 wt%, and more preferably 10-40 wt%, based on the total weight of the copolymer. When the content of the styrene unit satisfies the above range, the effect of reducing the viscosity of the conductive material dispersion is more excellent.

[0074] The alkylene unit can be represented by the following [Formula 5].

[0075] [Formula 5]

[0076]

[0077] In the above Formula 5, n may be an integer of 1 to 50, and preferably an integer of 3 to 30.

[0078] The content of the alkylene unit may be 90 wt% or less, preferably 0 wt% to 85 wt%, and more preferably 15-60 wt%, based on the total weight of the copolymer. When the content of the alkylene unit satisfies the above range, the effect of reducing the viscosity of the conductive material dispersion is more excellent.

[0079] Specifically, the auxiliary dispersant copolymer according to the present invention may be a copolymer including an oxyalkylene unit and a styrene unit, a copolymer including an oxyalkylene unit and an alkylene unit, or a copolymer including an oxyalkylene unit, a styrene unit and an alkylene unit.

[0080] According to the research of the present inventors, when a copolymer including a combination of the above-mentioned specific units is used together with a nitrile-based copolymer as a main dispersant, the viscosity of the conductive material dispersion is significantly reduced compared to the case where the nitrile-based copolymer is used alone or the case where different types of auxiliary dispersants are used together with the nitrile-based copolymer.

[0081] Meanwhile, the above-mentioned auxiliary dispersant copolymer of the present invention can be prepared by a copolymer preparation method well known in the art. For example, the auxiliary dispersant copolymer can be prepared by polymerizing a compound capable of inducing each unit, or can be prepared by reacting a compound comprising each unit via an acid-base reaction, etc.

[0082] The compound capable of inducing an oxyalkylene unit may be, for example, a polyalkylene glycol such as polyethylene glycol and polypropylene glycol, or an alkylene oxide compound such as (poly)ethylene oxide and (poly)propylene oxide, but is not limited thereto.

[0083] The compound capable of inducing styrene units may be, for example, styrene, α-methylstyrene, vinyltoluene, chloromethylstyrene, chlorostyrene, bromostyrene, vinylbenzenesulfonate, methoxymethylstyrene, benzyl (meth)acrylate, and the like, but is not limited thereto.

[0084] The compound capable of inducing the alkylene unit may be, for example, an alkyl (meth)acrylate monomer, an olefin monomer, and the like. Examples of the alkyl (meth)acrylate monomer may include, but are not limited to, methyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, octadecyl (meth)acrylate, isobornyl (meth)acrylate, and the like.

[0085] Examples of the olefin monomer may include propylene, butene, pentene, hexene, heptene, octene, nonene, decene, dodecene, tridecene, tetradecene, octadecene, and the like, but are not limited thereto.

[0086] Meanwhile, as a compound including each unit, for example, polyalkylene glycol, polyalkylene-styrene copolymer, styrene-maleic anhydride copolymer, polyalkylene imine, a surfactant including oxyalkylene and / or alkylene units, and the like may be used, but the present invention is not limited thereto.

[0087] Meanwhile, the weight average molecular weight of the auxiliary dispersant may be 800-50,000 g / mol, preferably 800-30,000 g / mol. When the weight average molecular weight of the auxiliary dispersant satisfies the above range, the effect of reducing the viscosity of the conductive material dispersion is excellent.

[0088] Meanwhile, in the conductive material dispersion of the present invention, the primary dispersant and the auxiliary dispersant may be included in a weight ratio of 30:70 to 90:10, preferably a weight ratio of 50:50 to 90:10, and more preferably a weight ratio of 60:40 to 90:10. When the content of the primary dispersant is less than the above range, the dispersion of the conductive material cannot be smoothly achieved, and thus the viscosity improvement effect is not significant. In addition, when the ratio of the primary dispersant in all dispersants is 50% or more, the viscosity improvement effect is more excellent.

[0089] (3) Dispersion medium

[0090] The dispersion medium may be an organic solvent including any one or two or more kinds of heteroatoms selected from the group consisting of nitrogen atoms (N) and oxygen atoms (O) having unshared electron pairs.

[0091] Specifically, the dispersion medium can be: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol and octanol; a diol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,4-diol, 1,6-diol, 1,8-diol, 1,2-diol, 1,4-diol, 1,6-diol, 1,8 ... Alcohol, 1,3-butanediol, 1,5-pentanediol and hexanediol; Polyols such as glycerol, trimethylolpropane, pentaerythritol and sorbitol; Glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether and tetraethylene glycol monobutyl ether; Ketones such as acetone, methyl ethyl ketone, methyl acetone and cyclopentanone; Esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone. Any one of them or a mixture of two or more of them can be used. When considering the miscibility with the electrode slurry, N-methylpyrrolidone (NMP) is particularly preferred.

[0092] The conductive material dispersion of the present invention including the above-mentioned components can be prepared by mixing a carbon-based conductive material, a primary dispersant, an auxiliary dispersant and a dispersion medium. At this time, mixing can be carried out by a typical mixing method, specifically, a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a nail crusher, a TK mixer or the like can be used. There is no particular restriction on the mixing order of the components. That is, the conductive material dispersion of the present invention can be prepared in the following manner: a carbon-based conductive material is added to a dispersion medium, and then a primary dispersant and an auxiliary dispersant are added thereto, and then mixed; first, a primary dispersant and an auxiliary dispersant are added to a dispersion medium, and then a carbon-based conductive material is mixed with them; or a primary dispersant, an auxiliary dispersant and a carbon-based conductive material are added to a dispersion medium and then mixed.

[0093] Meanwhile, during the above-mentioned mixing process, cavitation dispersion treatment may be performed to increase the dispersibility of the carbon-based conductive material. Cavitation dispersion treatment is a dispersion treatment method that utilizes shock waves generated by the collapse of vacuum bubbles formed in water when high energy is applied to a liquid. According to this method, dispersion can be achieved without damaging the properties of the carbon-based conductive material. Specifically, cavitation dispersion treatment may be performed by ultrasound, an airflow mill, or a shear dispersion treatment.

[0094] At the same time, the dispersibility of the carbon-based conductive material is affected by the type and specific surface area of ​​the carbon-based conductive material used, and therefore, it is necessary to appropriately adjust the content of the carbon-based conductive material and the dispersant according to the specific surface area of ​​the carbon-based conductive material used in order to obtain an excellent viscosity reduction effect. Therefore, the present inventors have repeatedly conducted research and found that when the specific surface area of ​​the carbon-based conductive material and the content of each component satisfy the specific relationship represented by the following equation (1), the viscosity reduction effect can be obtained.

[0095] Specifically, preferably, the conductive material dispersion according to the present invention is configured so that the specific surface area of ​​the carbon-based conductive material and the contents of the carbon-based conductive material and the dispersant in the conductive material dispersion satisfy the following equation (1).

[0096] Equation (1): 0.07A ≤ {(W1+W2) / W3}×100 ≤ 0.3A

[0097] At this time, in the above equation (1), W1 represents the weight % of the main dispersant in the conductive material dispersion, W2 represents the weight % of the auxiliary dispersant in the conductive material dispersion, W3 represents the weight % of the conductive material in the carbon-based conductive material dispersion, and A is the BET specific surface area (unit: m 2 / g) value.

[0098] When the conductive material dispersion satisfies the above equation (1), the carbon-based conductive material can be sufficiently wetted, so that the effect of reducing the viscosity of the conductive material dispersion can be maximized.

[0099] According to one embodiment, the conductive material dispersion according to the present invention may include a nitrile-based copolymer with a weight average molecular weight of 10,000-100,000 g / mol as a main dispersant, a copolymer having an oxyalkylene unit, a styrene unit and an alkylene unit as an auxiliary dispersant, and a carbon-based conductive material with a BET specific surface area of ​​150-200 m 2 When the primary dispersant, the auxiliary dispersant and the carbon-based conductive material satisfy the above combination, the effect of reducing the viscosity is excellent.

[0100] electrode

[0101] Next, the electrode according to the present invention will be described.

[0102] The electrode according to the present invention includes an electrode active material layer formed from an electrode paste composition, which contains an electrode active material, a conductive material dispersion, and a binder. Specifically, the electrode includes an electrode current collector and an electrode active material layer formed on the electrode current collector, where the electrode active material layer can be formed from an electrode paste composition containing an electrode active material, a conductive material dispersion, and a binder.

[0103] At this time, the conductive material dispersion is the conductive material dispersion according to the present invention as described above. The description of the conductive material dispersion is the same as above, so its detailed description will be omitted. Hereinafter, only the remaining components will be described.

[0104] The electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, copper, stainless steel, aluminum, nickel, or titanium surface-treated with one of carbon, nickel, titanium, silver, and the like, calcined carbon, or the like can be used.

[0105] The electrode current collector generally can have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the electrode current collector to improve the adhesion of the negative electrode active material. In addition, the electrode current collector can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric bodies.

[0106] Meanwhile, the electrode active material (a) included in the electrode active material layer can be a positive electrode active material or a negative electrode active material commonly used in the art, and its type is not particularly limited.

[0107] For example, as the positive electrode active material, lithium oxides containing lithium and one or more metals such as cobalt, manganese, nickel, or aluminum can be used. More specifically, the lithium oxides can be: lithium manganese-based oxides (e.g., LiMnO2, LiMn2O, etc.); lithium cobalt-based oxides (e.g., LiCoO2, etc.); lithium nickel-based oxides (e.g., LiNiO2, etc.); lithium nickel manganese-based oxides (e.g., LiNi 1-Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiNi Z1 Mn 2-Z1 O4 (where 0 < Z1 < 2), etc.); lithium nickel cobalt-based oxides (e.g., LiNi 1-Y2 Co Y2 O2 (where 0 < Y2 < 1), etc.); lithium manganese cobalt-based oxides (e.g., LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co Z2 O4 (where 0 < Z2 < 2), etc.); lithium nickel cobalt manganese-based oxides (e.g., Li(NiP1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2 )O4 (where 0 < P2 < 2, 0 < Q2 < 2, 0 < R2 < 2, P2 + Q2 + R2 = 2), etc.); or lithium nickel cobalt manganese other metal (M) oxides (e.g., Li(Ni P3 Co Q3 Mn R3 M 1 S )O2 (where M 1 is selected from the group consisting of Al, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Nb, Mg, B, W and Mo, and P3, Q3, R3 and S are each the atomic fraction of an independent element, and 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, P3 + Q3 + R3 + S = 1), etc.) and the like, and may include any one of them or a mixture of two or more of them.

[0108] Meanwhile, the negative electrode active material can be a carbonaceous material, such as artificial graphite, natural graphite, graphitized carbon fiber and amorphous carbon; metal compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd and Si alloys and Sn alloys or Al alloys; metal oxides that can be doped and undoped with lithium, such as SiO v (0 < v < 2), SnO2, vanadium oxides and lithium vanadium oxides; or composites comprising metal compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one of them or a mixture of two or more of them can be used. In addition, a thin film of metallic lithium can be used as the negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon and the like can all be used as carbon materials.

[0109] Based on the total solid content in the electrode paste composition, the electrode active material can be included in an amount of 70 - 99% by weight, preferably 80 - 98% by weight. When the content of the positive electrode active material satisfies the above range, excellent energy density, electrode adhesion and conductivity can be achieved.

[0110] Adhesive is used to ensure the adhesion between electrode active materials or between electrode active materials and current collector. Any adhesive commonly used in the art can be used, and its type is not particularly limited. Adhesive can be, for example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers and the like, and any one of them or a mixture of two or more of them can be used.

[0111] Based on the total solid content in the electrode slurry composition, the binder may be included in an amount of 5 wt % or less, and preferably may be included in an amount of 1-3 wt %. When the content of the binder satisfies the above range, excellent electrode adhesion may be achieved while minimizing the increase in electrode resistance.

[0112] Meanwhile, if necessary, the electrode slurry composition may further include a solvent to control viscosity, etc. At this time, the solvent may be water, an organic solvent, or a mixture thereof. The organic solvent may be, for example: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, and octanol; diols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-Butanediol, 1,5-pentanediol and hexanediol; polyols such as glycerol, trimethylolpropane, pentaerythritol and sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether and tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl acetone and cyclopentanone; and esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone. Any one of them and a mixture of two or more of them can be used, but the organic solvent is not limited thereto.

[0113] The solvent may be included in an amount such that the solid content in the electrode slurry becomes 60-85 wt %, preferably 65-80 wt %. When the solid content of the electrode slurry is less than 60 wt %, the electrode loading may be reduced, thereby increasing the process cost, binder migration may occur, thereby reducing the electrode adhesion, and coating defects may occur. Meanwhile, when the solid content of the electrode slurry is greater than 85 wt %, the viscosity of the electrode slurry becomes too high, so that the processability may be deteriorated and coating defects may occur.

[0114] The electrode according to the present invention can be manufactured by the following method: by applying an electrode slurry composition including the above-mentioned components, and then drying, thereby forming an electrode active material layer. Specifically, the electrode active material layer can be formed by a method in which the electrode slurry is applied to an electrode collector and then dried, or by a method in which the electrode slurry is applied to a separate support and then the film obtained by peeling off the support is laminated on the electrode collector. If necessary, after the electrode active material layer is formed by the above method, a process of rolling the electrode active material layer can be additionally performed. At this time, taking into account the physical properties of the electrode finally manufactured, drying and rolling can be performed under appropriate conditions, and there are no special restrictions.

[0115] Lithium secondary battery

[0116] Next, a secondary battery according to the present invention will be described.

[0117] The secondary battery according to the present invention includes the electrode of the present invention described above. In this case, the electrode may be at least one of a positive electrode and a negative electrode. Specifically, the secondary battery according to the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. In this case, at least one of the positive electrode and the negative electrode may be the electrode of the present invention described above. Preferably, the electrode of the present invention may be a positive electrode.

[0118] Since the electrode according to the present invention has been described above, a detailed description thereof will be omitted. Hereinafter, only the remaining components will be described.

[0119] The separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in lithium secondary batteries. Specifically, as a separator, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed of glass fiber, polyethylene terephthalate fiber or the like having a high melting point. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used with a single layer or multilayer structure.

[0120] The electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten-type inorganic electrolyte, and the like, which can be used in the preparation of a lithium secondary battery, but is not limited thereto.

[0121] Specifically, the electrolyte may include a nonaqueous organic solvent and a lithium salt.

[0122] As the nonaqueous organic solvent, for example, aprotic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0123] In particular, in carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used because it is a high-viscosity organic solvent and has a high dielectric constant to dissociate lithium salts well. Since when such cyclic carbonates are mixed with linear carbonates (such as dimethyl carbonate and diethyl carbonate) having low viscosity and low dielectric constant in an appropriate ratio, an electrolyte with high conductivity can be prepared, so such cyclic carbonates are more preferably used.

[0124] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in a non-aqueous electrolyte solution. For example, as the anion of the lithium salt, one or more selected from the group consisting of the following can be used: - , Cl - ,I- 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - , and (CF3CF2SO2)2N - .

[0125] In the electrolyte, in order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be further included, for example, halogenated alkylene carbonate-based compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, ethylene glycol dimethyl ether (glyme), hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride and the like. Specific embodiments

[0127] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments set forth herein.

[0128] The specification of each component used in the following Examples and Comparative Examples is as follows.

[0129] (A) Main dispersant

[0130] (A1) Hydrogenated acrylonitrile-butadiene rubber (H-NBR) having a weight average molecular weight of 260,000 g / mol (weight ratio of acrylonitrile:hydrogenated butadiene=34:66) was used.

[0131] (A2) Hydrogenated acrylonitrile-butadiene rubber (H-NBR) having a weight average molecular weight of 34,000 g / mol (weight ratio of acrylonitrile:hydrogenated butadiene=34:66) was used.

[0132] (B) Auxiliary dispersant

[0133] As the auxiliary dispersant, a copolymer of each of the following (B1) to (B24) was used, and the weight ratio of the oxyalkylene unit, the styrene unit, the alkylene unit and other units in the copolymer of each of (B1) to (B24) and the weight average molecular weight of the copolymer were shown in the following Table 1. At this time, the content of each unit in the copolymer was measured by nuclear magnetic resonance (NMR).

[0134] (B1) Ethomeen 18 / 25 from Akzonobel Co., Ltd. was used.

[0135] (B2) A copolymer of polyethylene glycol and styrene (weight ratio of oxyalkylene unit:styrene unit=71.8:28.2, weight average molecular weight: 1,250 g / mol) was used.

[0136] (B3) A copolymer prepared by mixing 10 g of polyethyleneimine (manufacturer: Sigma-Aldrich, molecular weight: 1800 g / mol) and 10 g of AKYPO RO90 (Oleth-10 carboxylic acid, manufacturer: KAO chemicals) with 20 g of NMP was used, and then reacting the mixture at 80° C. for 20 hours.

[0137] (B4) A copolymer prepared by mixing 10 g of polyethyleneimine (manufacturer: Sigma-Aldrich, molecular weight: 1800 g / mol) and 6.6 g of AKYPO RO90 (Oleth-10 carboxylic acid, manufacturer: KAO chemicals) with 20 g of NMP was used, and then reacting the mixture at 80° C. for 20 hours.

[0138] (B5) A copolymer prepared by mixing 10 g of polyethyleneimine (manufacturer: Sigma-Aldrich, molecular weight: 1800 g / mol) and 3.3 g of AKYPO RO90 (Oleth-10 carboxylic acid, manufacturer: KAO chemicals) with 20 g of NMP was used, and then reacting the mixture at 80° C. for 20 hours.

[0139] (B6) Styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was used.

[0140] (B7) A copolymer prepared by the following method was used: 10 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was dissolved in 112.4 g of NMP, and then 0.459 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 18.2 g of Ethomeen O / 12 from Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0141] (B8) A copolymer prepared by the following method was used: 5 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was dissolved in 114.6 g of NMP, and then 0.23 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 23.7 g of Ethomeen O / 12 from Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0142] (B9) A copolymer prepared by the following method was used: 10 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was dissolved in 125.1 g of NMP, and then 0.45 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 21.4 g of Ethomeen C / 15 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0143] (B10) A copolymer prepared by the following method was used: 5 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was dissolved in 107.4 g of NMP, and then 0.23 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 21.9 g of Ethomeen C / 25 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0144] (B11) A copolymer prepared by the following method was used: 5 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), weight ratio of styrene unit:maleic anhydride unit = 75:25, weight average molecular weight: 1,900 g / mol) was dissolved in 113.1 g of NMP, and then 0.23 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 21.9 g of Ethomeen T / 25 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0145] (B12) A copolymer prepared by the following method was used: 7 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), molar ratio of styrene unit:maleic anhydride unit = 1.3:1, weight average molecular weight: 1,600 g / mol) was dissolved in 113.2 g of NMP, and then 0.54 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 21.4 g of Ethomeen O / 12 from Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0146] (B13) A copolymer prepared by the following method was used: 4 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), molar ratio of styrene unit:maleic anhydride unit = 1.3:1, weight average molecular weight: 1,600 g / mol) was dissolved in 143.2 g of NMP, and then 0.309 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 31.9 g of Ethomeen 18 / 25 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0147] (B14) A copolymer prepared by the following method was used: 7 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), molar ratio of styrene unit:maleic anhydride unit = 1.3:1, weight average molecular weight: 1,600 g / mol) was dissolved in 128.1 g of NMP, and then 0.54 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 25.2 g of Ethomeen C / 15 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0148] (B15) A copolymer prepared by the following method was used: 4 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), molar ratio of styrene unit:maleic anhydride unit = 1.3:1, weight average molecular weight: 1,600 g / mol) was dissolved in 133.6 g of NMP, and then 0.309 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 5 g of Ethomeen C / 25 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0149] (B16) A copolymer prepared by the following method was used: 4 g of a styrene-maleic anhydride copolymer (Sigma-Aldrich Co. Ltd., poly(styrene-co-maleic anhydride), molar ratio of styrene unit:maleic anhydride unit = 1.3:1, weight average molecular weight: 1,600 g / mol) was dissolved in 141.2 g of NMP, and then 0.309 g of water was added thereto, and they were mixed at 80° C. for 10 minutes, and then 31.4 g of Ethomeen T / 25 of Akzonobel Co., Ltd. was added thereto, and the mixture was reacted at 80° C. for 20 hours.

[0150] (B17) 8 g of styrene monomer, 12.08 g of dimethylaminoethyl methacrylate and 2.9 g of NMP were mixed in a 100 mL flask, and the mixture was nitrogen bubbled for 10 minutes. In addition, azobisisobutyronitrile (AIBN) dissolved in NMP at 10 wt% was bubbled to extract 21.02 g of azobisisobutyronitrile, and the extracted azobisisobutyronitrile was added to the flask, and then heated and mixed at 90°C for polymerization reaction for 5 hours to prepare a polymerization solution. A copolymer prepared by the following method was used: 1 g of the polymerization solution and 1.55 g of AKYPO RO20 (Olethcarboxylic acid, manufacturer KAO chemicals) were mixed, and then the mixture was reacted at 80°C for 20 hours.

[0151] (B18) A copolymer prepared by mixing 1 g of the polymerization solution prepared in (B17) and 2.04 g of AKYPO RO50 (Olethcarboxylic acid, manufacturer: KAO chemicals) was used, and then reacting the mixture at 80°C for 20 hours.

[0152] (B19) A copolymer prepared by mixing 2 g of the polymerization solution prepared in (B17) and 1.64 g of AKYPO RO50 (Olethcarboxylic acid, manufacturer: KAO chemicals) was used, and then reacting the mixture at 80°C for 20 hours.

[0153] (B20) used a copolymer prepared by mixing 2 g of the polymerization solution prepared in (B17) and 1.65 g of AKYPO RO20 (Olethcarboxylic acid, manufacturer: KAO chemicals), and then reacting the mixture at 80°C for 20 hours.

[0154] (B21) A polystyrene polymer (Sigma-Aldrich Co. Ltd., weight average molecular weight: 35.00 g / mol) was used.

[0155] (B22) 5.27 g of styrene monomer, 19.97 g of dimethylaminoethyl methacrylate and 24.82 g of NMP were mixed in a 100 mL flask, and the mixture was nitrogen bubbled for 10 minutes. In addition, azobisisobutyronitrile (AIBN) dissolved in NMP at 10 wt % was bubbled to extract 0.52 g of azobisisobutyronitrile, which was then added to the flask, and then heated and mixed at 90° C. to perform a polymerization reaction for 5 hours, thereby preparing a copolymer. The copolymer prepared as described above was used.

[0156] (B23) 8 g of styrene monomer, 12.08 g of dimethylaminoethyl methacrylate and 2.9 g of NMP were mixed in a 100 mL flask, and the mixture was nitrogen bubbled for 10 minutes. In addition, azobisisobutyronitrile (AIBN) dissolved in NMP at 10 wt % was bubbled to extract 21.02 g of azobisisobutyronitrile, which was then added to the flask, and then heated and mixed at 90° C. to perform a polymerization reaction for 5 hours, thereby preparing a copolymer. The copolymer prepared as described above was used.

[0157] (B24) A copolymer prepared by dissolving 5 g of polyacrylic acid (Wako pure chemical Co., Ltd., molecular weight 1,800 g / mol) in 94.3 g of NMP, then adding 18.6 g of oleylamine (Sigma-Aldrich Co., Ltd.) thereto, and then reacting the mixture at 80° C. for 20 hours was used.

[0158] [Table 1]

[0159]

[0160] (C) Conductive materials

[0161] (C1) uses a BET specific surface area of ​​185m 2 / g of carbon nanotubes (CNT, manufacturer: LG Chem).

[0162] (C2) uses a BET surface area of ​​250 m 2 / g of carbon nanotubes (CNT, manufacturer: LG Chem).

[0163] (C3) uses a BET specific surface area of ​​130m 2 / g of carbon black (manufacturer: DENKA).

[0164] Examples 1 to 34

[0165] In a 1L container, the components listed in Table 2 below as the primary dispersant (A), the auxiliary dispersant (B) and the conductive material (C) were added to N-methylpyrrolidone at the weight % described in [Table 2] below to prepare 500 g of a mixed solution. Thereafter, a saw type impeller (VMA-GETZMANN Co., Ltd., DISPERMAT CN20) having a diameter of 80 mm was used to mix at 5,000 rpm for 60 minutes, and then a bead mill (Netzsch Co., Ltd., Mini-Cer) filled with 500 g of 1 mm zirconia beads was used to grind for 60 minutes.

[0166] Comparative Examples 1 to 5

[0167] In a 1L container, the components listed in Table 3 below as the main dispersant (A), the auxiliary dispersant (B) and the conductive material (C) were added to N-methylpyrrolidone at the weight % described in [Table 3] below to prepare 500 g of a mixed solution. Thereafter, a saw type impeller (VMA-GETZMANN Co., Ltd., DISPERMAT CN20) having a diameter of 80 mm was used to mix at 5,000 rpm for 60 minutes, and then a bead mill (Netzsch Co., Ltd., Mini-Cer) filled with 500 g of 1 mm zirconia beads was used to grind for 60 minutes.

[0168] The viscosity of the conductive material dispersion prepared in each Example and Comparative Example was measured using a viscometer (TOKI Co., Ltd., viscometer TV-22) at 25° C. and 1 rpm, and then the viscosity reduction rate relative to the reference solution was measured according to the following equation (2).

[0169] Equation (2): Viscosity reduction rate (%) = {(viscosity of reference solution - viscosity of conductive material dispersion) / viscosity of reference solution} × 100

[0170] In the above equation (2), different solutions are used as reference solutions depending on the type of conductive material used in preparing the conductive material dispersion.

[0171] Specifically, when measuring the viscosity reduction rate of a conductive material dispersion in which the (C1) component is used as a conductive material, a solution in which 3.77 wt % of the conductive material (C1) and 0.76 wt % of the primary dispersant (A1) are mixed in N-methylpyrrolidone is used as a reference solution, and the viscosity of the reference solution is 17.09 Pa·s.

[0172] When measuring the viscosity reduction rate of a conductive material dispersion in which the (C2) component is used as the conductive material, a solution in which 1.85 wt % of the conductive material (C2) and 0.37 wt % of the primary dispersant (A1) are mixed in N-methylpyrrolidone is used as a reference solution, and the viscosity of the reference solution is 8.61 Pa·s.

[0173] When measuring the viscosity reduction rate of a conductive material dispersion in which the (C3) component is used as the conductive material, a solution in which 14.45 wt % of the conductive material (C3) and 1.45 wt % of the primary dispersant (A1) are mixed in N-methylpyrrolidone is used as a reference solution, and the viscosity of the reference solution is 6.36 Pa·s.

[0174] The measurement results are shown in [Table 2] and [Table 3] below.

[0175] [Table 2]

[0176]

[0177]

[0178] [Table 3]

[0179]

[0180] It can be confirmed from the above Table 2 that when the copolymer including the oxyalkylene unit and the styrene unit and / or the alkylene unit is used, the viscosity of the conductive material dispersion is reduced by 20% or more compared with the reference solution.

[0181] However, as shown in Table 3, in the case of Comparative Examples 1 to 5, in which the copolymer not satisfying the composition of the present invention was used as the auxiliary dispersant, the viscosity of the conductive material dispersion was increased instead.

[0182] The following content corresponds to the original claims in the parent application and is now incorporated herein as part of the specification:

[0183] 1. A conductive material dispersion, comprising:

[0184] Carbon-based conductive materials;

[0185] dispersants; and

[0186] Dispersion medium,

[0187] The dispersant comprises a primary dispersant and an auxiliary dispersant, wherein:

[0188] The primary dispersant is a nitrile-based copolymer; and

[0189] The auxiliary dispersant is a copolymer including an oxyalkylene unit and at least one of a styrene unit and an alkylene unit.

[0190] 2. The conductive material dispersion according to item 1, wherein the auxiliary dispersant comprises 9 wt% to 85 wt% of oxyalkylene units.

[0191] 3. The conductive material dispersion according to item 1, wherein the auxiliary dispersant is a copolymer having a weight average molecular weight of 800-50,000 g / mol.

[0192] 4. The conductive material dispersion according to item 1, wherein the primary dispersant and the auxiliary dispersant are included in a weight ratio of 30:70 to 90:10.

[0193] 5. The conductive material dispersion according to item 4, wherein the primary dispersant and the auxiliary dispersant are included in a weight ratio of 60:40 to 90:10.

[0194] 6. The conductive material dispersion according to item 1, wherein in the conductive material dispersion, when the content of the primary dispersant is W1 (wt%), the content of the auxiliary dispersant is W2 (wt%), the content of the carbon-based conductive material is W3 (wt%), and the BET specific surface area value of the conductive material is A (m 2 / g), the following equation (1) is satisfied:

[0195] Equation (1): 0.07A≤{(W1+W2) / W3}×100≤0.3A.

[0196] 7. The conductive material dispersion according to item 1, wherein the primary dispersant is a nitrile-based copolymer having a weight average molecular weight of 10,000 to 500,000 g / mol.

[0197] 8. The conductive material dispersion according to item 1, wherein the nitrile-based copolymer is acrylonitrile-butadiene rubber.

[0198] 9. The conductive material dispersion according to claim 1, wherein the carbon-based conductive material has a BET specific surface area of ​​100-1000 m 2 / g of carbon nanotubes.

[0199] 10. The conductive material dispersion according to item 1, wherein the carbon-based conductive material has a BET specific surface area of ​​30-1000 m 2 / g of carbon black.

[0200] 11. The conductive material dispersion according to item 1, wherein the dispersion medium is an organic solvent including one or more heteroatoms selected from the group consisting of nitrogen atoms and oxygen atoms.

[0201] 12. The conductive material dispersion according to item 1, wherein:

[0202] The primary dispersant is a nitrile-based copolymer having a weight average molecular weight of 10,000-100,000 g / mol;

[0203] The auxiliary dispersant is a copolymer including oxyalkylene units, styrene units and alkylene units; and

[0204] The carbon-based conductive material has a BET specific surface area of ​​150-200 m 2 / g of carbon nanotubes.

[0205] 13. An electrode comprising: an electrode active material layer formed from an electrode slurry composition, the electrode slurry composition comprising an electrode active material, the conductive material dispersion according to any one of items 1 to 12, a binder, and a solvent.

[0206] 14. An electrode according to claim 13, wherein the electrode is a positive electrode.

[0207] 15. A lithium secondary battery comprising: a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the electrode described in item 13.

Claims

1. A conductive material dispersion, include: Carbon-based conductive materials; Dispersants; and Dispersion medium, The dispersant comprises a primary dispersant and an auxiliary dispersant, wherein: The primary dispersant is a nitrile-based copolymer; and The auxiliary dispersant is a copolymer including at least one of a styrene unit and an alkylene unit and an oxyalkylene unit. 2 . The conductive material dispersion according to claim 1 , wherein the auxiliary dispersant comprises 9 to 85 wt % of oxyalkylene units. 3 . The conductive material dispersion according to claim 1 , wherein the auxiliary dispersant is a copolymer having a weight average molecular weight of 800-50,000 g / mol. 4 . The conductive material dispersion according to claim 1 , wherein the primary dispersant and the auxiliary dispersant are included in a weight ratio of 30:70 to 90:

10. 5 . The conductive material dispersion according to claim 4 , wherein the primary dispersant and the auxiliary dispersant are included in a weight ratio of 60:40 to 90:

10.

6. The conductive material dispersion according to claim 1, wherein in the conductive material dispersion, when the content of the primary dispersant is W1 (wt%), the content of the auxiliary dispersant is W2 (wt%), the content of the carbon-based conductive material is W3 (wt%), and the BET specific surface area value of the carbon-based conductive material is A (m 2 / g), the following equation (1) is satisfied: Equation (1): 0.07A≤{(W1+W2) / W3}×100≤0.3A. 7 . The conductive material dispersion according to claim 1 , wherein the primary dispersant is a nitrile-based copolymer having a weight average molecular weight of 10,000-500,000 g / mol.

8. The conductive material dispersion according to claim 1, wherein the nitrile-based copolymer is acrylonitrile-butadiene rubber.

9. The conductive material dispersion according to claim 1, wherein the carbon-based conductive material has a BET specific surface area of ​​100-1000 m 2 / g of carbon nanotubes.

10. The conductive material dispersion according to claim 1, wherein the carbon-based conductive material has a BET specific surface area of ​​30-1000 m 2 / g of carbon black. 11 . The conductive material dispersion according to claim 1 , wherein the dispersion medium is an organic solvent including one or more heteroatoms selected from the group consisting of nitrogen atoms and oxygen atoms.

12. The conductive material dispersion according to claim 1, in: The primary dispersant is a nitrile-based copolymer having a weight average molecular weight of 10,000-100,000 g / mol; The auxiliary dispersant is a copolymer including oxyalkylene units, styrene units and alkylene units; and The carbon-based conductive material has a BET specific surface area of ​​150-200 m 2 / g of carbon nanotubes.

13. An electrode, include: An electrode active material layer formed from an electrode slurry composition, the electrode slurry composition comprising an electrode active material, the conductive material dispersion according to any one of claims 1 to 12, a binder, and a solvent. The electrode according to claim 13 , wherein the electrode is a positive electrode.

15. A lithium secondary battery, include: A positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the electrode of claim 13.